2021
DOI: 10.1002/cam4.4066
|View full text |Cite
|
Sign up to set email alerts
|

ALOX5‐5‐HETE promotes gastric cancer growth and alleviates chemotherapy toxicity via MEK/ERK activation

Abstract: This is an open access article under the terms of the Creat ive Commo ns Attri bution License, which permits use, distribution and reproduction in any medium, provided the original work is properly cited.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 26 publications
(14 citation statements)
references
References 29 publications
0
14
0
Order By: Relevance
“…ALOX5 was shown to regulate ferroptosis in cancer cells through lipid peroxidation ( 19 , 63 ). In gastric cancer and hepatocellular carcinoma, ALOX5 expression was significantly higher than that in normal tissues in the promotion of tumor progression ( 64 , 65 ). On the other hand, ALOX5 inhibition augments the efficacy of other chemotherapeutic agents in the treatment of gastric cancer.…”
Section: Discussionmentioning
confidence: 97%
“…ALOX5 was shown to regulate ferroptosis in cancer cells through lipid peroxidation ( 19 , 63 ). In gastric cancer and hepatocellular carcinoma, ALOX5 expression was significantly higher than that in normal tissues in the promotion of tumor progression ( 64 , 65 ). On the other hand, ALOX5 inhibition augments the efficacy of other chemotherapeutic agents in the treatment of gastric cancer.…”
Section: Discussionmentioning
confidence: 97%
“…Among the 8-gene signature of high immune cell infiltration (type C2), ALOX5 has been found to promote gastric cancer growth and attenuate chemotherapy toxicity [63], while in breast cancer, ALOX5 activation is associated with HER2 expression as well as mediates breast cancer growth and migration [64]. Recent studies have reported that the polymorphism of FCGR2A expression is associated with an increased risk of lung cancer [65].…”
Section: Discussionmentioning
confidence: 99%
“…The pathway with the largest number of associated genes is the mitogen-activated protein kinases (MAPKs) signaling pathway. Eight genes could regulate it, and they are AKAP2 [72], ALOX5 [63], GCGR [73], NLRP12 [74], NTSR1 [75], PF4 [76], SIGLEC12 [68] and TGM2 [77]. Wnt/β-catenin signaling pathway could be regulated by AKAP2 [55], ALOX5 [78] and TGM2 [79].…”
Section: Discussionmentioning
confidence: 99%
“…Fig 1 shows the increase of some metabolites, ARA included, which were positively or negatively impacted by the CRC spheroid in the presence of adipocytes. Furthermore, studies demonstrate the increase of 5-lipoxygenase (5-LOX), part of the ARA pathway, and its metabolite, 5-HETE, in tumor tissues of the prostate, pancreas, colon, stomach and cervix [41][42][43][44][45][46].…”
Section: Plos Onementioning
confidence: 99%